1968
DOI: 10.1038/bjc.1968.93
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and inhibition of the induction by 7,12-dimethylbenz(a)anthracene of mammary tumours in female Sprague-Dawley rats

Abstract: Images Fig. 6-9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The enzyme system can be enhanced in the rat liver by the administration of various inducers [17,25,28,29,32] thus producing increased amounts of metabolites as well as further derivatives. However, in further publications the involvement of DMBA hydroxylation in mammary tumor induction has been indicated and contradicted [2,6,16,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme system can be enhanced in the rat liver by the administration of various inducers [17,25,28,29,32] thus producing increased amounts of metabolites as well as further derivatives. However, in further publications the involvement of DMBA hydroxylation in mammary tumor induction has been indicated and contradicted [2,6,16,32].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme system can be enhanced in the rat liver by the administration of various inducers [17,25,28,29,32] thus producing increased amounts of metabolites as well as further derivatives. However, in further publications the involvement of DMBA hydroxylation in mammary tumor induction has been indicated and contradicted [2,6,16,32]. The com parison of DMBA and various immediate metabolites showed that both DMBA and 7-HOM-12MBA caused mammary cancer, although a shorter period was required for the induction of sarcomas by DMBA than its meta bolite; 12-HOM-7MBA, or 7,12-diHOMBA were inactive [2,16,33], Never theless it has been suggested that the carcinogenic activity of DMBA could be attributed to the formation of 7-HOM-12MBA and subsequent conver sion of this metabolite to an ether, yielding reactive ions at the site of action [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of lung cells to induce microsomal enzymes would seem to be advantageous in view of reports that prior administration of AHH-inducing agents to laboratory animals prevented tumorigenesis by BP (19) and induced AHH levels lead to rapid conversion to noncarcinogenic metabolites, then either inhibition or induction of the enzyme results in lower rates of tumor formation (14,(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…Two experimental models have been used mainly for this purpose: the formation of mammary tumors in rats given oral doses of Me2BzA, and the determination of skin tumor formation in mouse skin. Induction of increased polycyclic-hydrocarbon hydroxylase activity by several different flavones and other compounds before the administration of Me2BzA inhibits breast tumor formation* (13); SKF525-A, an inhibitor of microsomal enzyme activity, leads to an increased incidence of tumor formation (14). The formation of skin tumors in mice has been inhibited by pretreatment of the skin with 5,6-BzFl as an inducing agent and BzP as a carcinogen (15); pretreatment with 7,S-BzFl, an inhibitor of the enzyme or a weakly inducing compound has been responsible for the inhibition of tumors when given 5 min before treatment with Me2BzA (9).…”
Section: Discussionmentioning
confidence: 99%